2003
DOI: 10.1097/01.jom.0000094993.20914.d1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Lung, Eye, and Skin Lesions as Late Complications in 34,000 Iranians With Wartime Exposure to Mustard Agent

Abstract: Approximately 34,000 Iranians known to have sustained mustard agent exposure during the Iran-Iraq war of 1980-1988 and survived over a decade afterwards were screened for distribution of the most commonly occurring medical problems. In order of greatest incidence, these include lesions of the lungs (42.5%), eyes (39.3%), and skin (24.5%). Within each subpopulation, patients were ranked according to severity of lesions. Twenty-three percent to 37% of patients exhibited at least mild coverage, with 1.5% to 4.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
214
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 290 publications
(230 citation statements)
references
References 30 publications
8
214
0
3
Order By: Relevance
“…Long-term pulmonary complications from sulfur mustard (SM) exposure have included chronic obstructive pulmonary disease (COPD), chronic bronchitis, bronchiolitis obliterans, bronchiectasis, airway hyper-reactivity, and lung fibrosis (Balali-Mood et al, 2005;Emad & Rezaian, 1997;Ghanei et al, 2008a,b;Khateri et al, 2003). The SM-exposed patients suffer from pulmonary disorders due to previous documented exposure to a single high dose of SM gas they faced during the Iran-Iraq conflict in 1987.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term pulmonary complications from sulfur mustard (SM) exposure have included chronic obstructive pulmonary disease (COPD), chronic bronchitis, bronchiolitis obliterans, bronchiectasis, airway hyper-reactivity, and lung fibrosis (Balali-Mood et al, 2005;Emad & Rezaian, 1997;Ghanei et al, 2008a,b;Khateri et al, 2003). The SM-exposed patients suffer from pulmonary disorders due to previous documented exposure to a single high dose of SM gas they faced during the Iran-Iraq conflict in 1987.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for the observed clinical results may be due to long term side-effects of poisoning, reported by other investigators, which include severe respiratory complications and the resulting oxygenation disorder that may ensue (5,14,15). Therefore, it is expected for the victims to develop polycythemia, to compensate for the hypoxemia, but according to previous studies, this type of manifestation, which can be caused by destruction of RBCs, was not noted.…”
Section: Discussionmentioning
confidence: 82%
“…Approximately 95% are males who were between 17 and 30 y of age at the time of exposure. 3 The subjects enrolled in this study had severe obstructive pulmonary disease referred to as mustard airway disease, a late complication of mustard gas exposure. Previous pathological and radiological studies have shown bronchiolitis obliterans 4,5 to be the main airway disease in mustard gas-exposed cases, and imaging studies also indicated other airway diseases such as bronchiectasis, tracheobronchomalacia, and tracheobronchial stenosis.…”
Section: Introductionmentioning
confidence: 99%